Relation of Volume of Hemorrhage With Mortality Within First 48 Hours in Hemorrhagic Stroke (KYAMC Journal, 2021)
Background: Hemorrhagic stroke accounts for 10-15% of all strokes with higher mortality rates than cerebral infarction. Intracerebral hemorrhage has a reported 30-day mortality of 44% to 51%, with almost half of the death occurs within the first 48 hours. Advanced age, low level of consciousness, large volume of hemorrhage has been linked with poor outcome.Objectives: To predict early outcome of hemorrhagic stroke patient in relation with age, Glasgow Coma Scale, volume of hemorrhage and ventricular extension.Materials and Methods: Hospital based prospective study carried out in hundred hemorrhagic stroke patients. The formula of ABC/2 was used to calculate hemorrhage volume in bedside by using CT scan.Results: 1st month mortality rates of hemorrhagic stroke was 44% with 45.45% of patients died within the first 48 hours of onset. Mean age of patients of hemorrhagic stroke was 61.2 ± 13.88 years. Mortality rate of intracerebral hemorrhage after age of 60 was 51.06% in 1st month. Volume of intracerebral hemorrhage was the strongest predictor of both 48 hours and 30 days mortality. Using three categories of intracerebral hemorrhage (X for < 30 ml, Y for 30 - 50 ml and Z for > 50 ml group) calculated by ABC/2 formula showed 100% mortality rate in Z group, 50% in Y group and only 12% mortality rate in X group in 1st month. Among all death, 61.5% of Z group 25% of Y group and 16.67% of patients of X group died within 48 hours. Two categories of Glasgow Coma Scale (≤ 8 and ≥ 9) were used and shown death rates 80.77% in GCS ≤ 8 and 4.55% in GCS ≥ 9 in 1st month.Conclusion: Volume of intracerebral hemorrhage in combination with advanced age, initial Glasgow Coma Scale is a powerful and easy to use in both 48 hours and 1st month mortality in patients with spontaneous intracerebral hemorrhage.KYAMC Journal. 2021;12(3): 127-132